Reactions of Calcium Phosphate with Some Fruit Juices - Rao, T.V.R.K. (Asian Journal of Chemistry, 2010)
Reactions of calcium phosphate with some fruit juices, viz., juice of jamiri, gagal and kagzi lemons (Citrus limon), orange (Citrus aurantium), sweet orange (Citrus sinensis), cherries (Prunus cerasus) and grapes (Vitis viuifera) have been studied. Solubility of calcium phosphate in the fruit juices has been determined. Conductometric titrations evidenced complexation of calcium phosphate by the complexone (hydroxy acid) of fruit juices. The juices have been standardised with respect to their hydroxy acid content by a comparative method. A calcium phosphato citrate (1 : 3) complex has been isolated and characterised from the reaction mixture of calcium phosphate and kagzi lemon juice.